Characterization of sulfur compounds and antiviral activity against Tomato brown rugose fruit virus (ToBRFV) of Italian "Vessalico" garlic compared to other cultivars and landrace. (15th January 2023) - Iobbi, Valeria; Santoro, Valentina; Maggi, Norbert; Giacomini, Mauro; Lanteri, Anna Paola; Minuto, Giovanni; Minuto, Andrea; Fossa, Paola; De Tommasi, Nunziatina; Bisio, Angela; Drava, Giuliana
Abstract: In this study the Italian garlic "Aglio di Vessalico" was compared with the French cultivars Messidrôme and Messidor, whose cloves are used every year by the growers of Vessalico (Imperia, Italy) for sowing, and with the geographically adjacent "Aglio di Caraglio". UHPLC-Q-trap analyses of the extracts of these commercial garlic accessions showed similar profiles for sulfur compounds, highlighting the presence of typical molecules of stored garlic. HC, PCA and SOM, applied to the LC/MS data, allowed to separate the garlic accessions, confirming similarities between Vessalico and French accessions, while Caraglio formed a more compact group. All garlic extracts showed ability to deactivate Tomato brown rugose fruit virus (ToBRFV) infectivity, as a possible consequence of disassembly of the virus coat protein (CP). Molecular docking showed a strong interaction of the sulfur compounds characteristic of aged extracts with a high number of residues into ToBRFV CP binding site, interfering with virulence progress. Graphical abstract: Image 1 Highlights: UHPLC-Q-trap characterization of organosulfur compounds of garlic extracts was performed. Multivariate analysis highlighted differences among garlic cultivars and ecotypes. Agricultural and local conditions are important for composition of sulfur compounds. Garlic extracts showed antiviral activity against ToBRFV. Antiviral activity of garlic extracts is related to aging and compound synergism.